2019
DOI: 10.7705/biomedica.4701
|View full text |Cite
|
Sign up to set email alerts
|

Estrés oxidativo en células endoteliales inducido por el suero de mujeres con diferentes manifestaciones clínicas del síndrome antifosfolípido

Abstract: Introducción. El síndrome antifosfolípido se caracteriza por la presencia persistente de anticuerpos antifosfolípidos y manifestaciones clínicas de trombosis o morbilidad gestacional, las cuales se asocian con estrés oxidativo y disfunción endotelial.Objetivo. Evaluar los marcadores de estrés oxidativo en células endoteliales, inducidos por el suero de mujeres con diferentes manifestaciones clínicas del síndrome antifosfolípido y analizar la capacidad antioxidante de los sueros.Materiales y métodos. Se incluye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Since both depolarization and hyperpolarization involve dissociation of the electron transport chain and an increase of oxygen consumption, these conditions can be harmful to the cell through the induction of oxidative or reductive stress ( Guo et al, 2011 ; Oaks et al, 2016 ; Zorova et al, 2018 ). We previously reported that serum from women with PM/VT increased the intracellular and mitochondrial production of ROS in HUVECs ( Velásquez et al, 2019 ), the same group of patients whose IgGs induced the high MMP (hyperpolarization) in this study. Taken together, these findings suggest a mechanism by which aPL from women with PM/VT induced HUVEC oxidative stress.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Since both depolarization and hyperpolarization involve dissociation of the electron transport chain and an increase of oxygen consumption, these conditions can be harmful to the cell through the induction of oxidative or reductive stress ( Guo et al, 2011 ; Oaks et al, 2016 ; Zorova et al, 2018 ). We previously reported that serum from women with PM/VT increased the intracellular and mitochondrial production of ROS in HUVECs ( Velásquez et al, 2019 ), the same group of patients whose IgGs induced the high MMP (hyperpolarization) in this study. Taken together, these findings suggest a mechanism by which aPL from women with PM/VT induced HUVEC oxidative stress.…”
Section: Discussionsupporting
confidence: 68%
“…Human umbilical vein endothelial cells (HUVEC) were isolated from umbilical cords obtained from uncomplicated pregnancies based on a modified protocol by Jaffe et al (1973) and as previously described ( Velásquez et al, 2019 ; Gil-Villa et al, 2020 ). In brief, umbilical veins were perfused with 100 μg/ml type I collagenase (Invitrogen, Waltham, MA, United States) and incubated for 20 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical and laboratory features of women included in this study are outlined in Table 1 . Women in this study were classified as Pregnancy Morbidity/Vascular Thrombosis (PM/VT), women that fulfilled the clinical and laboratory revised Sapporo classification criteria for APS (n=7); Seronegative-Obstetric APS (SN-OAPS), women who present clinical features consistent with a diagnosis of obstetric APS but tested persistently negative for conventional anti-cardiolipin (aCL), anti-β2glicoprotein-I (aβ2GPI) and lupus anticoagulant (LA) tests[ 4 ], these women were positive for the non-criteria aPL[ 5 ] (n=8), and Pregnancy Morbidity/aPL- (PM/aPL-), women with a history of gestational morbidity, without autoimmune or chronic diseases, negative for both non-criteria aPL and conventional tests (n=10). These women were compared with a Normal Human Serum (NHS) group, healthy women with previous uncomplicated pregnancies (n= 7).…”
Section: Ase R Eportmentioning
confidence: 99%